Factors affecting the purchase intentions of luxury cars in Malaysia - Hamidi, Muhammad Hairul Ashraf (2021)
Luxury cars, the ultimate signalling tool for many successful Malaysians. In recent years, luxury cars have become a common sight on Malaysian roads, especially in urban-metropolitan areas. As Malaysians shift economically, the dream of owning a luxury car has become a reality for many high-earning Malaysians. Though such may be, the literature from the developing nation has been sparse at best. This dissertation sets out to study what are the factors that stimulate Malaysian consumers to buy luxury cars from a consumer behavioural aspect. The research wishes to bridge the gap between what literature has said and what empirical findings can bring to the table. In the past, multiple factors have been variables that contribute to luxury car purchase intentions. Yet, this dissertation will look at the factors in consideration of brand consciousness, materialism, social comparison, self-identification and brand image. Moreover, this research was outlined to study the effects of these variables towards purchase intentions. Next, this study utilized a quantitative method to gain data from the respondents. Particularly, online surveys were deployed out to 215 Malaysian respondents. This research implies that marketers can tune their marketing strategy and approach to fit the findings from this research paper.